The Politics of Lace in Kate Evans' Threads: From the Refugee Crisis (). Issue 1 (22nd October 2020) - Earle, Harriet
Abstract : Kate Evans' 2017 comic Threads: From the Refugee Crisis chronicles her visits to the 'Jungle' refugee camp in Calais, where she volunteered with a group of other British nationals to help build shelters and offer general assistance to those in the camp. The comic is bookended with double-page spreads that depict traditional lace making processes. Calais is particularly famous for lace production and it is a trade that has long been the domain of women. In addition, lace is used throughout the comic in the gutters of the pages. Using close textual and visual analysis, this article considers the use of lace throughout the comic. Beginning with a brief history of the fabric itself, it is argued that the use of lace provides a clear socio-political and cultural framework by which we can read the comic, positioning the stories of refugees within representational frameworks governed by white, European artistic and cultural production. Moreover, the lace can be read as a metaphor for the geopolitical interactions which led to the massive displacement of people and, so, the creation of 'the Jungle'.